IMPROVING ENGLISH LANGUAGE SKILLS OF YOUTH THROUGH THE "DOLZARB 90 KUNLIK" PROGRAM - Nazirova Minavar Anvarbekovna (TADQIQOTLAR, 2026)
Abstract English has become one of the most important languages for education, employment, and international communication. In Uzbekistan, various educational reforms have been introduced to improve young people’s foreign language skills. One such initiative is the "Dolzarb 90 Kunlik" (Relevant 90-Day Program), which aims to engage youth in productive educational activities during the summer period. This study examines the effectiveness of teaching English through the "Dolzarb 90 Kunlik" program. The research follows the IMRAD structure and analyzes the impact of intensive English instruction on learners’ language proficiency, motivation, and communication skills. The findings indicate that structured short-term programs significantly improve students’ confidence, vocabulary, and speaking ability.